Fresh takes on teaching literary elements : how to teach what really matters about character, setting, point of view, and theme - Smith, Michael W. (Michael William), 1954-; Wilhelm, Jeffrey D., 1959-; National Council of Teachers of English (New York : Scholastic, 2010)
Offers tools and strategies for teaching literary elements to middle and high school students, covering character, theme, point of view, and setting, and including activities.
Includes bibliographical references (p. 203-208).
Keywords: Literature -- Study and teaching (Secondary).; Language arts (Secondary) -- United States; Comparative literature -- Themes, motives; Character in literature; Setting (Literature).